Non-Negotiability in Conflict: Religious Zionist Attachments to Land and Temple in the Israeli-Palestinian Conflict - Zalzberg, Ofer (Trinity College Dublin. School of Religion. Irish School of Ecumenics, 2023)
A major reason for peacemaking failures has thus far been overlooked and understudied: policy makers and scholars tend to lack a nuanced understanding of non-negotiability, especially when they encounter conflict parties with expressivist worldviews and absolute commitments to deeply held values. The present research aims to explore how conflict transformation could address worldviews with such ?protected values? and the kinds of behavior they command. The critical failure to address these types of values becomes evident through the study of how religious Zionist attachments to the Land of Israel and the Temple Mount has shaped and continues to shape the Israeli-Palestinian conflict. The settlement movement and the Temple movements, which religious Zionists created precisely to prevent certain kinds of conflict resolution processes, dramatically transformed the history of Arab-Israeli relations by rendering the partition or sharing of the land and of the Temple Mount/Haram al-Sharif extremely difficult. This research employs qualitative methods to examine data collected through historical accounts of religious Zionist dimensions of the conflict as well 70 interviews with 18 religious Zionist rabbinic leaders (analyzed primarily through theological and morphological analysis). Based on insights from the interviews, the research project enhances knowledge of the scholarly conceptualization of protected values, the emergence of such values through their articulation by authoritative elites, and the consolidation of support for those values. The project highlights the potential of coupling peacemaking diplomacy with hermeneutics when crafting new political realities which cohere with protected values. It provides concrete examples for the religious Zionist case study for how diplomatic efforts could seek to design a peace architecture which respects the protected values; and how hermeneutic efforts could reinterpret the prohibition in such a way as to both preserve the integrity of the relevant entity and enable conflict-relevant tradeoffs. This research offers an alternative to the materialist pursuit of distributive compromises with an approach that combines diplomatic peacemaking and hermeneutics in ways which both retain and refine the protection of values. In so doing, it opens up a new direction for transforming worldview conflicts with overlapping protected values.
APPROVED
Keywords: Protected Values; Worldviews; Religious Zionism; Israeli-Palestinian Conflict; Conflict Studies